Perhitungan Harga Pokok Produksi Berdasarkan Metode Job Order Costing Untuk Penetapan Harga Pesanan Pada GRC Vino Al-Ghaniyyu - Salman, Kautsar Riza; Mawardah, Amelia; Shonhadji, Nanang; Sa’diyah, Halimatus; Sutisna, Entis (Jurnal KeDayMas: Kemitraan dan Pemberdayaan Masyarakat, 2024)
Based on interviews and observations at GRC Vino Al-Ghaniyyu as a partner, it is known that in determining the order price, it still uses a simple calculation of the cost of production and has not taken into account several cost components. An accurate calculation of the cost of production can produce a competitive order price, show real profits, and serve as evaluation material for subsequent orders. The cost of production method that is in accordance with the characteristics of MSMEs is job order costing. Community service activities aim to provide assistance in calculating the cost of production in accordance with the concept of cost accounting. Implementation methods include cost identification, calculation of the cost of production, and calculation of the selling price. The results of this community service activity are the calculation of the cost of production using job order costing obtained at Rp15,013,083. The provision of a profit of 40% of the cost of production will result in the determination of the order price of Rp21,018,317. The output of this community service is a report on the cost of production in the form of a job order cost sheet.